Leaving the Catholic Church: Cross-Sectional and Longitudinal Predictors of Leaving Intentions - Pummerer, Lotte (The international journal for the psychology of religion, 2026)
What predicts whether people are likely to leave the Catholic Church? We examine the role of different identification aspects and their interaction with acceptance of authority, possibility for change, and reputation of the Church in society. In a cross-sectional (N = 583) and longitudinal study with random intercept (N = 271) we find that specifically lower scores on the identification aspects of solidarity, satisfaction, and centrality predict leaving intentions. Cross-sectionally, the relationship between identification and leaving intentions is moderated by acceptance of authority, possibility for change, and reputation (NRange = 580–583). However, this moderation is not confirmed in longitudinal cross-lagged panel analyses (N = 263/195). Overall, findings point to self-investment aspects of identification as a crucial factor in predicting leaving intentions and emphasize the importance of assessing identification with the Church multi-dimensionally and longitudinally.